2009
DOI: 10.1371/journal.pone.0004725
|View full text |Cite
|
Sign up to set email alerts
|

β-Defensin-2 Protein Is a Serum Biomarker for Disease Activity in Psoriasis and Reaches Biologically Relevant Concentrations in Lesional Skin

Abstract: BackgroundPrevious studies have extensively documented antimicrobial and chemotactic activities of beta-defensins. Human beta-defensin-2 (hBD-2) is strongly expressed in lesional psoriatic epidermis, and recently we have shown that high beta-defensin genomic copy number is associated with psoriasis susceptibility. It is not known, however, if biologically and pathophysiologically relevant concentrations of hBD-2 protein are present in vivo, which could support an antimicrobial and proinflammatory role of beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 49 publications
12
144
2
4
Order By: Relevance
“…This might allow HIV-1 to 217 establish infection foci more effectively in individuals with higher copy number, and therefore higher 218 levels of hBD-2 protein. Furthermore, unlike the chemoattractant activity of hBD2 (typically at 25-219 100 ng/ml), the anti-HIV-1 activity of hBD2 is only at unphysiological concentrations (> 4µg/ml) 220 (Quiñones-Mateu et al 2003;Sun et al 2006), in contrast to physiological levels in serum and vaginal 221 fluid of less than 10ng/ml in healthy and infected conditions and <150ng/ml in serum from 222 inflammatory disease patients (Jansen et al 2009;Jiang et al 2012;Mitchell et al 2013 Furthermore, this effect is dependent on the copy number of KIR3DS1, with increased copies (in 236 combination with a HLA-Bw4-80I allele) show lower levels of HIV-1 viral load in clinical latency phase 237 (Alter et al 2007;Bashirova et al 2011;Pelak et al 2011b). This is an interesting example of 238 epistasis, where the effect of one allele is dependent on the presence of another allele at a 239 physically unlinked locus.…”
Section: Host Copy Number Variation and Hiv 151mentioning
confidence: 99%
“…This might allow HIV-1 to 217 establish infection foci more effectively in individuals with higher copy number, and therefore higher 218 levels of hBD-2 protein. Furthermore, unlike the chemoattractant activity of hBD2 (typically at 25-219 100 ng/ml), the anti-HIV-1 activity of hBD2 is only at unphysiological concentrations (> 4µg/ml) 220 (Quiñones-Mateu et al 2003;Sun et al 2006), in contrast to physiological levels in serum and vaginal 221 fluid of less than 10ng/ml in healthy and infected conditions and <150ng/ml in serum from 222 inflammatory disease patients (Jansen et al 2009;Jiang et al 2012;Mitchell et al 2013 Furthermore, this effect is dependent on the copy number of KIR3DS1, with increased copies (in 236 combination with a HLA-Bw4-80I allele) show lower levels of HIV-1 viral load in clinical latency phase 237 (Alter et al 2007;Bashirova et al 2011;Pelak et al 2011b). This is an interesting example of 238 epistasis, where the effect of one allele is dependent on the presence of another allele at a 239 physically unlinked locus.…”
Section: Host Copy Number Variation and Hiv 151mentioning
confidence: 99%
“…A correlation was also observed for the DEFB4 protein (hBD-2) in the serum of healthy individuals but not in psoriasis patients with active disease. 28 However, in patients suffering from inflammatory bowel disease, transcription of DEFB4 is more correlated with disease activity than with the CN. 29 In addition to CNV, sequence variations between copies (multisite variations, MSVs) 30 represent a further level of genomic complexity and are suggested to determine phenotypes, as SNPs do.…”
Section: Introductionmentioning
confidence: 99%
“…Our data are in accordance with recent findings (Watt et al, 2015), reporting that the levels of peripheral α-defensins are elevated in Alzheimer's disease. The copy number polymorphism of the DEFB4 gene has been reported to influence the production of hBD2 Hollox et al, 2008;Jansen et al, 2009;. Accordingly, in our study a significant linear correlation was found between the DEFB4 CN and the serum levels (p¼ 0.002; r 2 ¼0.196) or CSF levels (p ¼0.001; r 2 ¼0.222, respectively).…”
Section: Discussionsupporting
confidence: 59%